(untitled) - Shirer, William L. (New York, 1952)
Journalist-Author William L. Shirer wrote this surprisingly accurate look at Europe and the Western World at mid-century point (early 1950's). Readers see Europe as it recovered from devastating conflict (with help from the Marshall Plan), Germany was divided, and the Cold War was reality. Also, the U.S. was the undisputed economic engine, heavily influencing Europe and striving to contain communism.
Keywords: Description and travel,Politics and government; 1945-; Europe,Europe